Comprehensive Physiology 2012
DOI: 10.1002/cphy.c100073
|View full text |Cite
|
Sign up to set email alerts
|

Uriniferous Tubule: Structural and Functional Organization

Abstract: The uriniferous tubule is divided into the proximal tubule, the intermediate (thin) tubule, the distal tubule and the collecting duct. The present chapter is based on the chapters by Maunsbach and Christensen on the proximal tubule, and by Kaissling and Kriz on the distal tubule and collecting duct in the 1992 edition of the Handbook of Physiology, Renal Physiology. It describes the fine structure (light and electron microscopy) of the entire mammalian uriniferous tubule, mainly in rats, mice, and rabbits. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
66
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 56 publications
(72 citation statements)
references
References 621 publications
1
66
1
Order By: Relevance
“…The mosaic pattern was seen in all nephrons studied and is probably a developmental feature, and it is difficult to see any functional implications. This mosaic pattern may be similar to the features seen, e.g., at the CNT with a mixture of CNT cells, principal cells, and intercalated cells, as recently reviewed by Christensen et al (5).…”
Section: Discussionmentioning
confidence: 56%
See 1 more Smart Citation
“…The mosaic pattern was seen in all nephrons studied and is probably a developmental feature, and it is difficult to see any functional implications. This mosaic pattern may be similar to the features seen, e.g., at the CNT with a mixture of CNT cells, principal cells, and intercalated cells, as recently reviewed by Christensen et al (5).…”
Section: Discussionmentioning
confidence: 56%
“…THE RAT KIDNEY HAS FOR MANY years been the target of a large number of functional and morphological investigations (10 -13, 17) and was recently reviewed (5). In recent years, especially the rat renal medulla has been the subject of intensive comparative structural-functional studies and computer modeling [see e.g., Refs.…”
mentioning
confidence: 99%
“…15 Although the genetic and cellular bases of cystinosis are clear, little is known on (1) the early structural and molecular changes in the complex kidney architecture leading to the Fanconi syndrome, (2) their significance for cystinosis progression along uriniferous nephron (reviewed in ref. 16 ), (3) the pathogenic role of cystine crystals, and (4) natural adaptation mechanisms. In cystinotic kidneys, Fanconi syndrome is generally attributed to PTC atrophy, starting at the glomerulotubular junction as swanneck deformities, but earlier functional defects caused by impaired gene expression were not considered.…”
mentioning
confidence: 99%
“…Our morphological and biochemical data are in concordance with biochemical study which showed strong level of PLAGL1 protein expression in the homogenates of human kidney papilla and medulla with weak expression in the kidney cortex [18]. It has been established that the epithelial cells of any given segment of the uriniferous tubule [divided according to the current morphological nomenclature into the proximal tubule, the intermediate (thin) tubule, the distal tubule and the collecting duct] are homogeneous and distinct for that segment, and that structural differences between them reflect the localization and function of transport proteins and receptors [19]. The different immunoreactivity of the PLAGL1 protein in the various parts of nephron and collecting tubules demonstrated in our study may express its involvement in specific transepithelial transport processes.…”
Section: Pnpla1mentioning
confidence: 99%